“Estudio técnico – Económico para la instalación de una planta de pilado y clasificado de arroz en el distrito de soritor” - Diaz Quiroz,Juan (1998)
Rice is a crop of great economic and nutritional importance for EPI ~ 5. San Martin is one of the main producers of rice to level national with a production total of 243 271 TM. In an area planted of 34 944 have in campaign 1 997. Occupying a 42% of you:. \ population farm and producing the 15'. il > of the production national. However 80% of the production of rice in husk comes to the coast to be milled and classified in modern Mills since the Miller Park in our area is obsolete, why the present dual project treat it in part that the rice is to be milled, generating employment and the use of the sub products (dust (, nelen and shell) in act1v1dades as the poultry, livestock and fish farmThe Valley of the Alto Mayo is the largest rice area in the San Martín region (65%) and Soritor and Havana districts produce more than 60% of rice production in the province of Moyobamba. The Committee of Soritor rice producers and habana...